2021
DOI: 10.3390/healthcare9040399
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Olfactory Function and Cognitive Impairment in Older Persons with Cognitive Impairments: A Cross-Sectional Study

Abstract: Olfactory function is an emerging topic of research in the fields of cognitive impairment and neurodegenerative diseases. We aimed to confirm the association between olfactory function and cognitive impairment by assessing the olfactory function of older persons with cognitive impairment and identify whether olfactory function is associated with cognitive impairment. For this study, we recruited 117 older people aged ≥65 years with cognitive impairments from a public hospital in Korea. We used the Korean versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In addition to congenital and idiopathic Anosmia, olfactory deficits are associated with a number of diseases, especially neurodegenerative diseases, such as Alzheimer's disease (AD) and Parkinson's disease (PD) 3 . Consistent with this, several clinical‐based, case–control, cross‐sectional studies have demonstrated associations of olfactory impairments (especially impairments identification dysfunction) with cognitive decline, mild cognitive impairment (MCI), or Alzheimer's disease, which are capable of reflecting the onset of cognitive decline, MCI and AD in cognitively normal adults 4–7 . Besides, several studies have demonstrated that olfactory impairment is associated with some diseases with neurological complications, such as obstructive sleep apnea, depression and so on 8–10 .…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…In addition to congenital and idiopathic Anosmia, olfactory deficits are associated with a number of diseases, especially neurodegenerative diseases, such as Alzheimer's disease (AD) and Parkinson's disease (PD) 3 . Consistent with this, several clinical‐based, case–control, cross‐sectional studies have demonstrated associations of olfactory impairments (especially impairments identification dysfunction) with cognitive decline, mild cognitive impairment (MCI), or Alzheimer's disease, which are capable of reflecting the onset of cognitive decline, MCI and AD in cognitively normal adults 4–7 . Besides, several studies have demonstrated that olfactory impairment is associated with some diseases with neurological complications, such as obstructive sleep apnea, depression and so on 8–10 .…”
Section: Introductionmentioning
confidence: 77%
“…The top of these terms based on their adjusted P-value are also displayed in chord plots (Figs. [4][5][6]. For KEGG pathway analysis, DEGs were mostly enriched in olfactory transduction (Fig.…”
Section: Functional Enrichment Analysis Of Degsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study that analyzed UPSIT scores in a normal population in Brazil, there was no significant association between education level and olfactory function, but it was reported that the participants’ economic status was associated with their ability to distinguish specific odors ( Silveira-Moriyama et al, 2010 ). Since the UPSIT involves identifying various types of odors, the results may vary depending on individual’s education level or the experience of exposure to a specific odor ( Silveira-Moriyama et al, 2010 ; Fornazieri et al, 2019 ; Park et al, 2021 ). Therefore, identifying culturally unfamiliar test odors and modifying and simplifying the test so that anyone can easily distinguish the options will be helpful to obtain more accurate test results.…”
Section: Discussionmentioning
confidence: 99%
“…Age-dependent decrease in the number of olfactory sensory neurons ( Mobley et al, 2014 ) and decline in neurogenesis capacity ( Enwere et al, 2004 ; Child et al, 2018 ), and neurodegeneration ( Hussain et al, 2018 ; Bhatia-Dey and Heinbockel, 2021 ) that parallel with OI ( Mobley et al, 2014 ) may increase the resistance to CSF flow ( Albeck et al, 1998 ; Norwood et al, 2019 ), negatively affecting solute drainage through the olfactory efflux route. Olfactory deficit has been linked to advanced physiological brain aging ( Devanand et al, 2015 ; Park et al, 2021 ) and has been associated with the forthcoming neurodegenerative disorders ( Baba et al, 2012 ; Yoo et al, 2019 ), although the mechanism behind these associations remains to be explored. The coexistence of OI and severe suppression of glymphatic transport with advancing age may provide new insights into these connections.…”
Section: Discussionmentioning
confidence: 99%